From Waste to Wealth: Entrepreneurial Ventures in Chitosan Extraction for Environmental Sustainability - Sulistyowati, Lilik; Syarif, Mohammad; Elvira, Marlon V.; Putrianti, Nabila Puspa; Andareswari, Novi; Krisnawati, Eny; Komarudin, Nurul Amri (Pandawan, 2024)
The degradation of water quality in the environment can be attributed to the discharge of wastewater from shrimp ponds. Conversely, solid waste in the form of shrimp shells presents an entrepreneurial opportunity through the extraction of chitosan, a substance with the potential to enhance water quality while contributing to environmental sustainability. Sampling for this study was conducted at the Vannamei Nusantara Gemilang pond, located in Tambakrejo Village, Malang Regency, East Java. The research employed an experimental methodology with a quantitative approach, supplemented by a literature review. Various doses of chitosan solutions were tested on shrimp pond wastewater. The optimal results were obtained at a dosage of 80 mg/L, significantly outperforming the untreated water. The test outcomes for the 80 mg/L dosage included: BOD (Biochemical Oxygen Demand) at 4.62 mg/L, Nitrite concentration at 0.045 mg/L, turbidity at 3.55 NTU (Nephelometric Turbidity Units), TSS (Total Suspended Solids) at 14.6 mg/L, TDS (Total Dissolved Solids) at 2974 mg/L, pH level at 6.31, and temperature at 31.40°C. Notably, the Total Dissolved Solids (TDS) levels did not meet quality standards, highlighting the need for further process optimization. These findings emphasize the potential of chitosan extraction as a sustainable solution, while also underscoring the importance of continued research into the economic feasibility of this waste-to-wealth approach. Further studies are necessary to refine the wastewater treatment process, quantify the economic benefits, and ensure the long-term viability of this entrepreneurial venture in environmental sustainability.